MODELING LEARNING THEORY DEVELOPMENT SOCIAL BANDURA IN LEARNING FOR MATHEMATICS CLASS V STUDENT AT SDN 30 PAGUYAMAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This study aims to determine the effectiveness of modeling the development of bandura social learning theory in mathematics learning for fifth grade students at SDN 30 Paguyaman. The research method used is research and development or Research and Development (R&D) which goes through 4 stages of implementation, namely, initial study, product development, field testing, and revision. The results of hypothesis testing showed that there was an increase in students' social learning in Mathematics from 16.7% to 26.8% in stage I and then increased again to 45.65% in stage II after the revision was made. This proves that the hypothesis of the development of the Bandura model of social learning in Mathematics for grade V students at SDN 30 Paguyaman is acceptable.